Explaining invasiveness from the extent of native range: new insights from plant atlases and herbarium specimens. Issue 1 (14th December 2012) - Lavoie, Claude; Shah, Manzoor A.; Bergeron, Alexandre; Villeneuve, Paul; van Kleunen, Mark
Abstract Aim We tested the relationship between the extent of the native range and the success (number of occurrences) in the introduced range of European vascular plant species naturalized in the province of Québec (Canada). We hypothesized that the performance of models linking native range size and species invasiveness can be improved if residence time and climate tolerance are taken into account. Methods The extent of the native range (Europe, Asia) was estimated using plant atlases. The number of occurrences in the introduced range (Québec) was estimated using the number of herbarium specimens stored in herbaria. Herbarium specimens were also used to obtain residence time. Plant hardiness was used as an indicator of the suitability of a species to the climate of the introduced range. Multiple linear regression models, corrected to take into account phylogenetic biases, were used to calculate correlations between the extent of the native range and the number of occurrences in the introduced range. Results The larger the native distribution area in Eurasia, the greater the number of occurrences (herbarium specimens) in Québec. The shorter the residence time and the less hardy the plant, the fewer the number of occurrences. In all models tested, the phylogenetic structure explained a significant proportion of the variance, but its influence decreased as the number of species or area studied (Europe versus Eurasia) increased. Main conclusions The extent of the native range is a good explanatory variable for the invasion success of vascular plants, especially once other factors (residence time, climate tolerance, phylogeny) are taken into account. Thus, a model using these variables could be used by environmental managers to flag species warranting further investigation. With the emergence of online databases, gathering the required information is becoming easier and cheaper. As online databases continue to improve and new analytical tools are developed, this approach will become even more powerful.